PENGARUH PENAMBAHAN CAMPURAN DAUN BAYAM MERAH (Amaranthus tricolor) DAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) TERHADAP KUALITAS BAKSO AYAM BROILER - Sari Gando Hidayati; Rudi Kusuma; Fira Faradillah (Jurnal Embrio, 2026)
This study aimed to determine the effect of adding a mixture of red spinach leaves (Amaranthus tricolor) and white oyster mushrooms (Pleurotus ostreatus) on the quality of broiler chicken meatballs. The research was conducted at the LL. DIKTI Region X Laboratory, Jl. Khatib Sulaiman, Gunung Pangilun, Alai Parak Kopi, North Padang District, Padang City, West Sumatra. The method used in this study was an experimental design using a Completely Randomized Design (CRD) consisting of 6 treatments with 3 replications. The treatments applied in this study were as follows:P1 = 0% Red Spinach Leaves + 0% White Oyster Mushrooms from 1000 g of meat (Control) P2 = 0% Red Spinach Leaves + 20% White Oyster Mushrooms from 1000 g of meat P3 = 5% Red Spinach Leaves + 15% White Oyster Mushrooms from 1000 g of meat P4 = 10% Red Spinach Leaves + 10% White Oyster Mushrooms from 1000 g of meat P5 = 15% Red Spinach Leaves + 5% White Oyster Mushrooms from 1000 g of meat P6 = 20% Red Spinach Leaves + 0% White Oyster Mushrooms from 1000 g of meat The variables observed in this study were protein content, moisture content, and fat content of the broiler chicken meatballs. Based on the results, the addition of red spinach leaves and white oyster mushrooms had a significant effect (P<0.05) on the moisture and fat content of the chicken meatballs. The addition also had a highly significant effect (P<0.01) on the protein content of the meatballs. The best treatment in this study was P5 (15% red spinach leaves + 5% white oyster mushrooms), which resulted in a moisture content of 51.17%, protein content of 8.70%, and fat content of 9.99%. Conclusion: The best treatment in this study was P5 (15% red spinach leaves + 5% white oyster mushrooms), which achieved a moisture content of 51.17%, protein content of 8.70%, and fat content of 9.99%.